DENTAL STATUS OF ORAL CAVITY OF BUKHARAGIPS WORKERS, DEVELOPMENT OF WAYS OF PREVENTION - Norova M.B. (Journal of new century innovations, 2022)
Diseases of the oral cavity are a common pathology that leads to the loss of teeth, the formation of foci of chronic odontogenic infection and other disorders both in the maxillofacial region and in the body as a whole. Serious medical and social consequences of inflammatory periodontal diseases and the absence of noticeable positive shifts in their mass prevention determine the need to deepen and concretize ideas about the etiology and pathogenesis of these diseases [1].